Patients' Educational Aspects by Nursing Graduates' Point of View - Bēta, Gunta; Līdaka, Anita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Strategies of patients’ educational process are extensive. Student nurses get involved in the patients’ educational process with the competences obtained during their study process and personal understanding about the approach to the patient as a unique personality when planned operational objectives are set or the educational process happens unexpectedly in situational context. Situational context is not as significant in qualitative patients’ education as appropriately chosen educational means and methods, as well as confidence about the patients’ educational outcome.